Diagnostic Performance of Frequency-Domain Optical Coherence Tomography to Predict Functionally Significant Left Main Coronary Artery Stenosis. (15th November 2021) - Bouki, Konstantina P.; Vlad, Delia I.; Goulas, Nikolaos; Lambadiari, Vaia A.; Dimitriadis, George D.; Kotsakis, Athanasios A.; Barοutsi, Kyriaki; Toutouzas, Konstantinos P.
Abstract : Aims . The aim of this study was to assess the safety and diagnostic efficacy of frequency-domain optical coherence tomography (FD-OCT) in identifying functional severity of the left main coronary artery (LM) stenosis determined by fractional flow reserve (FFR). Methods and Results . 101 patients with LM lesion (20–70% diameter stenosis angiographically) underwent FFR measurement and FD-OCT imaging of the LM. The following parameters were measured by FD-OCT in the LM: reference lumen area (RLA), reference lumen diameter (RLD), minimum lumen area (MLA), minimum lumen diameter (MLD), % lumen area stenosis, and % diameter stenosis. The LM lesions were analyzable by FD-OCT in 88/101 (87.1%) patients. FFR at maximum hyperemia was ≤0.80 in 39/88 (44.3%) patients. FFR values were correlated significantly with FD-OCT-derived LM lumen parameters. An MLA cutoff value of 5.38 mm 2 had the highest sensitivity and specificity of 82% and 81%, respectively, followed by an MLD of 2.43 mm (sensitivity 77%, specificity 72%) and AS of 60% (sensitivity 72%, specificity 72%) for predicting FFR <0.80. Conclusions . FD-OCT is a safe and feasible imaging technique for the assessment of LM stenosis. An FD-OCT-derived MLA of ≤5.38 mm 2 strongly predicts the functional severity of an LM lesion.